Sosialisasi Pemanfaatan Limbah Botol Plastik Untuk Kerajinan Celengan (Studi Kasus: RA Nurul Iman Bintang Alam Karawang) - Muhammad Alif Lukman Hidayat; Novia Rahmadhani; Putri Sekar Hamidah (KREATIF: Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
Community service activities are carried out at RA Nurul Iman Bintang Alam Karawang. This research aims to provide knowledge and increase understanding about waste and how to use it. The method used in community service activities is the gamification method. Gamification is the delivery of material related to learning to manage plastic bottle waste by practicing making simple piggy banks so that RA students can manage money from an early age. The service was carried out by three students from the Faculty of Engineering, Industrial Engineering Study Program, Singaperbangsa University, Karawang. This activity was attended by 14 students from class A and class B. Apart from that, there was also a socialization method, which consisted of an introduction to the material, a pre-test, and a post-test related to plastic waste management so that children could learn more about waste and be able to implement waste. the plastic bottle. The results of socialization on the use of plastic bottle waste from the pre-test and post-test work, the pre-test got an average score of 76.785 while the post-test got an average of 87.5. Based on these results, it can be seen that there has been an increase in RA Nurul Iman's students' understanding of waste and how to use it.